O-013 The pulsar vascular aneurysm neck reconstruction device for bifurcation aneurysms: in vitro study and first clinical experience. (4th July 2012) - Tateshima, S; Turk, A; Ceratto, R; Ferrario, A; Lylyk, P
Abstract : Introduction: We present the in vitro and first clinical results of a novel aneurysm neck reconstruction device specifically designed to treat bifurcation aneurysms. Method: The Pulsar Vascular Aneurysm Neck Reconstruction Device (ANRD) is a T-shaped, self-expanding, permanent implant made of nitinol with a uniquely open architecture that maintains the luminal patency of two bifurcation branches while holding a coil mass in place in the aneurysm. Utilizing in vitro aneurysm models, the following design aspects of the ANRD were optimized prior to first-in-man (FIM) use: number of nitinol struts, location of radiopaque markers, ability to position and reposition the device, pushability and microcatheter compatibility. Once the design of the ANRD was optimized and the safe delivery technique was established, the first clinical case was performed. Inclusion criteria for FIM cases includes unruptured, wide-necked intracranial aneurysms located at the basilar tip or carotid terminus with a diameter of the basilar or carotid artery appropriate for the device sizes available. FIM candidate cases were reviewed and approved by scientific advisory board members as well as the operator prior to the procedure. Clinical use of the ANRD was approved on a case-by-case basis. Results: Under fluoroscopic guidance, ANRDs of various sizes and designs were deployed in two basilar tip aneurysm models. The final version of the ANRD could be safely deployed in the models and the operator could steer the T-shaped device into both posterior cerebral arteries (PCAs). Following extensive in vitro testing and animal studies, the ANRD was successfully deployed in the first clinical cases. The FIM case was a female with an incidental basilar tip aneurysm, projecting anteriorly, measuring 10.3 mm in the largest diameter and 7.3 mm in the neck. Both PCAs were incorporated in the base of the aneurysm. One ANRD was delivered via a Marksman microcatheter and successfully placed at the neck of the basilar tip aneurysm. Coiling procedure was performed immediately after the placement of the ANRD. Immediate post coiling angiogram showed the tight packing of the aneurysm and the patency of both PCAs. The ANRD was stable during the coiling procedure without any radiographic signs of proximal migration by the pressure of the coil mass. Conclusion: The Pulsar Vascular ANRD provides excellent support to achieve tight coil packing in bifurcation wide-necked aneurysms. The FIM experience demonstrates the safety and feasibility of the ANRD concept. Results in the first group of patients including follow-up will be presented. Competing interests: S Tateshima: Pulsar Vascular. A Turk: Pular Vascular. R Ceratto: None. A Ferrario: None. P Lylyk: None.